EFFECT OF FINANCIAL ACCESS ON MSME BUSINESS PERFORMANCE, THE MODERATING ROLE OF FINANCIAL LITERACY (STUDY ON YOUTH ENTREPRENEURIAL GROUP IN JAMBI CITY) - Erwita Dewi; Hendriyaldi Hendriyaldi; Feni Tialonawarmi (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2022)
This study aims to determine the effect of financial access on business performance by testing the moderation effect of financial literacy on entrepreneurial youth groups in Jambi city. Using a survey research design, the questionnaire was distributed to 252 respondents. Hypothesis testing using PLS-SEM analysis tools with Smart PLS 2.0 software. The results of the study indicate that the entire hypothesis was accepted. This proves that financial access affects the business performance of MSMEs and financial literacy acts as a moderation variable.